Pengembangan Perangkat Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Berbasis Multiliterasi di SMA Negeri 2 Binjai - Irawan, Dandi; Nurmawati, Nurmawati; Rakhmawati, Fibri (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
This research is development research. This study aims to develop learning tools in the form of Learning Implementation Plans (RPP), Learner Worksheets (LKPD), and research instruments based on information skills on the subject of ecosystems for grade XI high school students and determine the quality of learning tools in terms of validity, practicality, and effectiveness. This development research was conducted based on the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation. The instruments used in this research are the lesson plan assessment questionnaire, the LKPD assessment questionnaire, and the assessment instrument assessment questionnaire to measure the validity value; the learning management observation sheet and student response questionnaire and observation sheet to measure practicality; and the learning outcomes test to measure the effectiveness of learning devices. The product trial was conducted at SMAN 2 Binjai on July 24, 2023, and August 7, 2023. The quality of the validity of the learning device meets the valid criteria indicated by the total average validity of the RPP, which is 89.29%, the total average validity of the LKPD, which is 75%, and the total average validity of the assessment instrument, which is 77.75%. The quality of the practicality of learning devices meets the practical criteria indicated by the average limited test results of 79.65% and the total average of field test results of 88.